2006
DOI: 10.1002/clc.4960291108
|View full text |Cite
|
Sign up to set email alerts
|

Acute improvement of aortic mechanics following hemodialysis in patients with chronic renal failure

Abstract: SummaryBackground: Evidence suggests that distensibility of the aorta is decreased in patients with end-stage renal failure, while the underlying mechanisms are unclear.Hypothesis: The purpose of the study was to evaluate the distensibility of the aorta in patients at the end stage of chronic renal failure before and after hemodialysis (HD).Methods: The diameter of the ascending aorta and distensibility were assessed in 48 patients on HD (31 men, 17 women, aged 45 ± 14 years) and in 27 normal subjects (17 men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Therefore, it is conceivable that a favorable effect on the vascular function tests of volume correction is offset by the simultaneous stimulation of the renin system and/or the sympathetic nervous system, resulting in the absence of an overall effect. Soubassi et al ( 27 ) showed that aortic distensibility, evaluated by M-mode echocardiography, in the parasternal long-axis view in patients with end-stage renal disease is significantly lower than in normal subjects, and it is significantly improved after hemodialysis. Hydration status and its frequent changes appear to be the major determinants of both pulse wave velocity and changes in pulse wave velocity in hemodialysis patients, and these changes are independent of blood pressure ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is conceivable that a favorable effect on the vascular function tests of volume correction is offset by the simultaneous stimulation of the renin system and/or the sympathetic nervous system, resulting in the absence of an overall effect. Soubassi et al ( 27 ) showed that aortic distensibility, evaluated by M-mode echocardiography, in the parasternal long-axis view in patients with end-stage renal disease is significantly lower than in normal subjects, and it is significantly improved after hemodialysis. Hydration status and its frequent changes appear to be the major determinants of both pulse wave velocity and changes in pulse wave velocity in hemodialysis patients, and these changes are independent of blood pressure ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ζ δζαζημθζηή αμνηζηή δζάιεηνμξ ιεηνζέηαζ ζηδκ ημνοθή ημο QRS ζοιπθέβιαημξ ημο δθεηηνμηανδζμβναθήιαημξ, πνζκ απυ ημ άκμζβια ηδξ αμνηζηήξ ααθαίδαξ ηαζ δ ζοζημθζηή αμνηζηή δζάιεηνμξ ιεηνζέηαζ ζημ ζδιείμ ηδξ πνυζεζαξ ηίκδζδξ ηδξ αμνηήξ (Δζηυκα 20). Ο ιέζμξ υνμξ ηζιχκ 5 έςξ 10 ζοζημθχκ πνδζζιμπμζείηαζ βζα ηδκ ηεθζηή ακάθοζδ (Barbetseas, 2006;Hirata, 1991;Sassalos, 2006, Soubassi, 2006Stefanadis, 1990Stefanadis, , 1994.…”
Section: γηαζωξαθηθό ππεξερνγξάθεκαunclassified
“…Αοηυ έπεζ ςξ απμηέθεζια, ηυζμ ηα ακαηθχιεκα ηφιαηα, υζμ ηαζ δ αμνηζηή ζηθδνία κα είκαζ επδνεαζιέκα ζε αζεεκείξ ιε ηεθζημφ ζηαδίμο κεθνζηή ακεπάνηεζα (Guérin, 2008;London, 1994;Marchais, 1993;Soubassi, 2006). Ζ αφλδζδ ειθακίγεηαζ ηαζ ζε δπζυηενα ζηάδζα κεθνζηήξ ακεπάνηεζαξ ηαζ ζηαδζαηά επζδεζκχκεηαζ υζμ δ ηάεανζδ ηνεαηζκίκδξ εθαηηχκεηαζ (Wang, 2005).…”
Section: τειηθνύ ζηαδίνπ λεθξηθή αλεπάξθεηαunclassified